Antibacterial Activity and Time-kill Kinetics of Positive Enantiomer of α-pinene Against Strains of Staphylococcus aureus and Escherichia coli - de Sousa Eduardo, Leticia; Farias, Ticiane C.; Ferreira, Siluana Benvindo; Ferreira, Paula Benvindo; Lima, Zilka Nanes; Ferreira, Savio Benvindo (Current Topics in Medicinal Chemistry, 2018)
Research on new antimicrobial agents is needed, as more and more microorganisms that cause antibiotic-resistant diseases are emerging commercially. In this group, we can find strains of Staphylococcus aureus and Escherichia coli, which are highly opportunistic species. Faced with this perspective, research using essential oils present in plants is emerging as a therapeutic alternative for the treatment of antimicrobial infections. Many of these oils have, in their composition, monoterpene α-pinene, that shows to have antibacterial activity. The purpose of this research is to evaluate the antimicrobial activity of the positive enantiomer of α-pinene against strains of Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. The methodologies used were: Disc-diffusion test, broth microdilution and bacterial death kinetics, all of which were standardized by CLSI. As a result, inhibition halos of 11 mm was obtained for the gram-positive strain and 12 mm for the gram-negative strain, both at the same concentration, 160 μl / ml. In addition, it was possible to observe with the death curve that the concentrations (1.25 μl/mL and 2.5 μl/mL of the (+)-α-pinene were able to eliminate the formation of bacterial colonies at one time of exposure of 2 hours for the E. coli strain. However, the death curve of the S. aureus strain was characterized by non-elimination of bacterial colonies at a 24 hours exposure time used for the experiment. Only amikacin evidenced its bacterial killing rate of all colonies within two hours of exposure. At the end, it was possible to verify the activity of the phytoconstituent against Escherichia coli strains ATCC 25922 and Staphylococcus aureus ATCC 25923, recommending the continuity of the studies with the use of different methodologies so that (+) - α-pinene in the future can be a compound used in antimicrobial therapy.
Keywords: Alpha-pinene